A new host plant for Cameraria ohridella Deschka & Dimic, 1986 (Lepidoptera: Gracilleriidae) - Aleh V. Sinchuk; Nadzeya V. Sinchuk; Svetlana V. Baryshnikova; Aliaksandr P. Kolbas (SHILAP, 2023)
The article deals with the study of host plants of Cameraria ohridella Deschka & Dimic, 1986, especially focusing on Belarus findings. For the first time, Acer saccharinum L., is recorded as a host plant. The cases of damaging other plants by this species as well as relationships of Gracillariidae with the plant family Sapindaceae are summarized.